(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: It is clinically important to review the state of patient’s paranasal sinuses, because a paranasal sinus disease creates the conditions for the onset of infection and its spread to the eyes and nose. This is especially important given a significant rise in the incidence of ocular inflammatory disease in recent years. Purpose: To identify computed tomography (CT) features of the paranasal sinuses in patients with idiopathic anterior uveitis. Material and Methods: One hundred and fifty patients with unilateral idiopathic anterior uveitis were involved in the study. Of these, 114 did not have signs of optic neuritis, and 36 had optic neuritis in the presence of uveitis. Patients underwent a routine eye examination (best-corrected visual acuity, ophthalmoscopy, biomicroscopy, intraocular pressure measurement, and Humphrey perimetry). Sinus CT scans were performed on a Philips Brilliance 16-slice scanner. Patients received treatment as per the Protocol for the Diagnosis and Treatment of Anterior Uveitis. Results: On the basis of CT reports, we identified CT features of the paranasal sinuses in patients with idiopathic anterior uveitis complicated by optic neuritis. There was CT evidence of maxillary sinus mucosal thickening and cerebrospinal fluid space expansion in all patients (n=36) with anterior uveitis complicated by optic neuritis. Fluid accumulation in the maxillary, frontal, and sphenoid sinuses was diagnosed in 41.7%, 11.1%, and 5.6%, respectively, of patients with anterior uveitis complicated by optic neuritis, which was significantly higher, than in patients with uncomplicated anterior uveitis. We found a significant and strong positive correlation of (a) maxillary sinus mucosal thickening with fluid accumulation in the maxillary sinus and cerebrospinal fluid space expansion and (b) decreased frontal sinus pneumatization and fluid accumulation in the frontal sinus. Conclusion: Sinus CT data enabled to find a significant association between the pattern of changes in the paranasal sinuses and the development of optic uveitis in patients with idiopathic anterior uveitis, which, generally, argues for performing sanitation of the sinuses when treating ocular inflammation.